Information technology fundamentals - Cruz, Mindalita O.; Rodriguez, Evelyn A.; Chua, Marissa G.; Apsay, Mary Regina B.; Albano, Gerald R.; Mangahas, Rhea B. (Jimczyville Publications, 2015)
"This book aims to develop and enhance student's ability to differentiate data and information, to understand the importance of data processing cycle and how they relate it in everyday transactions and the mastery of methods and categories of data processing. Generally, it emphasizes the significance of understanding the totality of its subordinating topics like hardware and software for the development of a diverse and enlightened society. Likewise, this book will hopefully help increase and open the possibility of enriching the students' formal training of this area."--Preface